Kolchin B.A. Wooden Artefacts from Medieval Novgorod - Макаров, Н.А. (Археологія, 1991)
Рецензія на книгу: Kolchin B.A. Wooden Artefacts from Medieval Novgorod // BAR International Series. — Oxford, 1989. — 495 p.